Microbial Residual Nitrogen Distribution in Brown Earth’s Aggregates as Affected by Different Maize Residues and Soil Fertility Levels - Xue, Pingluo; Pei, Jiubo; Ma, Nan; Wang, Jingkuan (Frontiers in Environmental Science, 2022)
As the hub of nitrogen cycling, microorganisms play an important role in N transformation and accumulation. Soil aggregates is important in improving soil fertility and preventing soil degradation due to it is an important index to main soil fertility. However, the allocation of microbial residual N and its contribution to total N in brown earth’s aggregates is still limited, especially the effects of different maize residue types returning and soil fertility levels. Focus on this, a 360-day lab incubation experiment at 25°C was carried out induced by adding maize roots and shoots into brown earth with low (L) and high (H) fertility, respectively. Soil samples were divided into macroaggregates (>250μm) and microaggregates (<250μm) by a dry-sieved method. The results showed that maize residue types had different effects on the fungal and bacterial residual N enrichment in soil aggregates. In macroaggregates, maize roots promoted the accumulation of fungal residual N, while in microaggregates, it was more beneficial to the accumulation of bacterial residual N. The high fertility soil could sequester more microbial residual N than low fertility soil, showing it was more conducive to the accumulation of bacterial residual N. The fungal residual N was more beneficially accumulated in low fertility soil. Regardless of the level of fertility, the proportion of N in total N with shoots treatment was higher than that with roots treatment, indicating that the above ground maize residues could better promote the metabolic process of microorganisms than the below ground ones.